Prevalence, clinical and laboratory characteristics of kidney disease in antiretroviral naïve HIV infected patients in South-South Nigeria - Okafor, UH; Unuigbe, EI; Chukwuonye, E (African Journal of Nephrology, 2015)
Background: Since the emergence of acquired immune deficiency syndrome (AIDS) about three decades ago, several renal disorders have been reported as common complications of the human immunodeficiency virus (HIV) infection. These renal disorders have resulted from diverse aetiologies. The aim of this study was to determine the prevalence, clinical and laboratory characteristics of antiretroviral naïve HIV-infected patients with impaired kidney disorder in South-South Nigeria. Methods: This was a cross-sectional study of antiretroviral naïve HIV-infected patients presenting at the University of BeninTeaching Hospital (UBTH), Benin City in South-South Nigeria for six months. The patients biodata, clinical,haematological and biochemical parameters were assessed. Their glomerular filtration rate using the six equation ofMDRD and protein excretion was calculated from protein-creatinine ratio. Data was analysed using statistical software program SPSS version 15.0. Results: Three hundred and eighty-three (383) patients with a mean age of 35.39 ± 8.78 years with a male/female ratio of 1:1 were studied. Of these 53.3% had evidence of kidney disorder. The main clinical features in patients with kidney disorder were evidence of fluid retention, urinary symptoms, pallor and encephalopathy. The mean systolic and diastolic blood pressure was 115.33 ± 17.17 and 72.33 ± 14.31 mmHg respectively. The mean estimated glomerular filtration rate (eGFR) was 52.5 ml/minute/1.73mm2. Patients with kidney disorder had worse proteinuria (p = 0.001), lower mean CD4 cell count, and packed cell volume (p = 0.019 and 0.001 respectively). Conclusion: Kidney disorder is a common complication in HIV-infected patients and they have clinical and laboratory anomalies. Screening of HIV/AIDS patients at point of diagnosis will facilitate early diagnosis of kidney disorders in them.